Magnetic proximity effect in Pr0.5Ca0.5MnO3/La0.7Sr0.3MnO3 bilayered films - Prokhorov, V.G.; Kaminsky, G.G.; Flis, V.S.; Kim, J.M.; Eom, T.W.; Park, J.S.; Lee, Y.P.; Svetchnikov, V.L. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2011)
The magnetotransport properties of Pr0.5Ca0.5MnO3/La0.7Sr0.3MnO3 bilayer, and Pr0.5Ca0.5MnO3 and La0.7Sr0.3MnO3 films, deposited on LaAlO 3 (001) substrate by pulse laser deposition have been investigated. The x-ray diffraction and high-resolution electron-microscopy analysis reveals that lattice parameters for the constituent sublayers in the bilayer are very close to that for the individual films. It was found that a ferromagnetictransition in the La0.7Sr0.3MnO3 sublayer significantly modifies the magnetotransport properties of thePr0.5Ca0.5MnO3 constituent sublayer, owing to occurrence of a magnetic proximity effect. The main evidences for this effect are an appearance of the exchange bias interaction between the constituent sublayers; a localized-to-itinerant crossover in the system of polarized electrons, which results in formation of the Griffiths-like ferromagnetic state; and an unusual polaron transport of carriers. The experimental results have been analyzed within the framework of modern theoretical approaches.